Adults who Report Childhood Ritualistic Abuse - Shaffer, Ruth E. (Journal of psychology and theology, 1992)
Therapists are finding an increasing number of patients uncovering memories of ritualistic forms of abuse from childhood. To gain a fuller understanding of this phenomenon, twenty outpatients reporting memories of ritualistic abuse were interviewed. Questions focused on the nature of the abuse and its perceived impact on interpersonal, occupational, and spiritual development. Reasons for entering psychotherapy as well as the nature and course of treatment were also discussed.Subjects entered therapy with similar psychological complaints. Reported psychiatric sequelae included dissociative, affective, somatization, and eating disorders. Abuse experiences were reported to have affected every aspect of their adult functioning. Subjects began therapy with little or no knowledge of the phenomenon of ritualistic abuse, and only one patient reported vague memories of ritualistic abuse before entering therapy. Reports from this sample reflect striking convergence among subjects and with data from previous research and clinical reports. A composite clinical case study is presented based on these data.